The Design and Development of an Expert System Prototype for Enhancing Exam Quality - DeCarlo, Paul Jarrod; Rizk, Nouhad (International Journal of Advanced Corporate Learning (iJAC), 2010)
This paper discusses the development of an expert system prototype for use in college institutions. Our aim is to enhance exam quality and student performance by obtaining metrics pertaining to assignments, study materials, textbooks, and lecture quality, then learning dynamically from this information to create a human-readable course evaluation. The goal is to obtain a model which can be applied to courses in which students struggle, so we can identify ways to enhance the most determining factor of their grade: the quality of the exam. This expert system will serve as a prototype for a larger, more comprehensive automated system which will be proposed to enhance curricula.